Young "antisemites" and "rescuers in Nazi-occupied Soviet Belarus: dynamics of children's behavior in the Holocaust - Saal, Yuliya von (Eastern european holocaust studies, 2025)
Children were direct witnesses of the Holocaust “by bullets” in occupied Eastern Europe - and sometimes more than that. They were capable of roles and actions that have little in common with our traditional romanticized ideas and expectations about “innocent childhood”. This article is arguing for a more complex understanding of how children and adolescents confronted the Holocaust in the occupied Soviet Union. Minors, like adults, continuously faced the decision to passively watch acts of discrimination, to participate in them, or even to take part in humiliating and harassing Jews - or, conversely, to come to their aid. In this respect, youngsters were more than just victims or “bystanders”. The range of behaviors was very wide, and it is important to realize that children’s agency had different consequences for the Jewish population.
Online veröffentlicht: 30. Oktober 2025
Gesehen am 18.02.2026